2021
DOI: 10.1080/0886022x.2021.1881554
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-sensing receptor promotes calcium oxalate crystal adhesion and renal injury in Wistar rats by promoting ROS production and subsequent regulation of PS ectropion, OPN, KIM-1, and ERK expression

Abstract: Objectives To explore the mechanism of calcium-sensing receptors (CaSRs) during the development of nephrolithiasis. Materials and methods Wistar rats were treated with ethylene glycol to induce calcium oxalate crystallization, and gadolinium chloride (GdCl 3 , an agonist of CaSR) and NPS 2390 (an antagonist of CaSR) were added. Oxidative stress (OS) and calcium oxalate crystals in the kidney were observed. CaSR expression and the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Experimental and clinical evidence has established that oxidative stress plays an important role in cytokine/chemokine secretions and podocyte/mesangial cell injury, leading to glomerular fibrosis and kidney failure. 26 , 27 Our present findings demonstrated that the 5/6Nx-injured kidney tissues with and without chronic stress had increased levels of p22 Phox and gp91 Phox genes and proteins, as well as oxidative stress production. p22 Phox and gp91 Phox are important membrane-type subunits of NADPH oxidase.…”
Section: Discussionsupporting
confidence: 55%
“…Experimental and clinical evidence has established that oxidative stress plays an important role in cytokine/chemokine secretions and podocyte/mesangial cell injury, leading to glomerular fibrosis and kidney failure. 26 , 27 Our present findings demonstrated that the 5/6Nx-injured kidney tissues with and without chronic stress had increased levels of p22 Phox and gp91 Phox genes and proteins, as well as oxidative stress production. p22 Phox and gp91 Phox are important membrane-type subunits of NADPH oxidase.…”
Section: Discussionsupporting
confidence: 55%
“…Calcium-sensing receptors (CaSR) were involved in the induction of kidney calculi related proteins. Calculi related proteins and ERK were upregulated in the kidney of rats treated with Calcium oxalate and cell apoptosis may lead to crystal adhesion on the surface of kidney cells to form calculi [24] . MicroRNAs (miRNAs) are important regulatory factors of gene expression, which play a key role in the occurrence and development of tumors and can also regulate ERK signal, which is usually overexpressed in cancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Increased urinary excretion of calcium ions is an important factor in the formation of calcium stones [24,33]. The calcium-sensing receptor (CaSR) plays a role in inhibiting calcium reabsorption and promoting the precipitation of CaP and oxalate when stimulated by elevated serum calcium levels [34,35]. Three claudin genes, namely claudin-14, claudin-16, and claudin-19, are involved in calcium ion transport in the thick ascending limb of Henle and have been linked to renal diseases, such as hypercalciuria, kidney stones, and bone mineral loss.…”
Section: Regulation Of Calcium Metabolismmentioning
confidence: 99%